LEARNER AUTONOMY: DRAWING TOGETHER THE THREADS OF SELF-ASSESSMENT, GOAL-SETTING AND REFLECTION (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
The concept of learner autonomy has been central to the Council of Europe’s thinking about language teaching and learning since 1979, when Henri Holec wrote Autonomy and foreign language learning (cited here as Holec 1981). Holec began by defining learner autonomy as the “ability to take charge of one’s own learning”, noting that this ability “is not inborn but must be acquired either by ‘natural’ means or (as most often happens) by formal learning, i.e. in a systematic, deliberate way”, and pointing out that “To take charge of one’s learning is to have […] the responsibility for all the decisions concerning all aspects of this learning […]” (Holec 1981, p.3).